Identifikasi Lalat Buah (Diptera: Tephritidae) serta Serangannya terhadap Beberapa Galur dan Varietas Tanaman Cabai ( Capsicum annum l.) Di Desa Pancasari, Sukasada, Buleleng - SANTIATMA, I MADE YESTA; SUMIARTHA, I KETUT; SUSILA, I WAYAN; SUDIARTA, I PUTU; UTAMA, MADE SUPARTHA; MARIYONO, JOKO; LUTHER, GREG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
ABSTRACT Identification of Fruit Flies (Diptera: Tephritidae) and It’s Damage Against to Some Lines and Varieties of Chili Plants ( Capsicum annum L.) In  Pancasari Village, Sukasada District, Buleleng Regency The research was conducted in the Field and in the Laboratory. Studies conducted in the laboratory of integrated pest management Faculty of Agriculture, Udayana University, concerning identification of fruit fly in the laboratory of Agricultural Quarantine Ist Class, Denpasar. The field research was conducted in the Pancasari village, Sukasada district, Buleleng regency, which was implemented in September to December 2014. The purpose of this study to determine the species of fruit flies that damage some lines and varieties of chili plants tested, to determine the percentage of fruit fly damage in some lines and varieties of chili plants, and to determine the yield of the each lines and varieties of chili plants were tested. This study used a randomized block design (RBD) with eighteen treatments and three replications. The results show  that the damage percentage of the highest fruit fly pest was found in line AVPP 1003-B with the percentage of 66.49%, while the  lowest line percentage was found in Kencana variety with a percentage of 23.82%. The fruit fly species found in the test lines and  varieties of chili plants ( Capsicum annum L.) is Bactrocera carambolae and B. papayae . The highest yields are found in line AVPP 0207 with an average yields of 202.99 grams / plant and the lowest was found in AVPP lines 0906 with an average of 66.64 grams  / plants.   Keywords: chili, the percentage of damage, Bactrocera carambolae, Bactrocera papayae.